2023
DOI: 10.1002/adhm.202202989
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Management of Metastatic Tumors by Robust Co‐Delivery of 5‐Fluorouracil/MicroRNA‐10b Inhibitor Using EGFR‐Targeted Nanovehicles

Abstract: Invasion and metastasis are the leading causes of death of patients with CRC. 5-Fluorouracil is widely used in clinic practice as the basic chemotherapy drug for CRC. However, it is inefficient in inhibiting tumor metastasis. MicroRNA-10b is uninvolved in regulating the growth of primary tumors; however, it could induce early tumor metastases and is a key regulator of chemotherapeutic resistance to 5-FU. A multifunctional nanovehicle that can carry small molecule drugs not only through the hydrophobic pockets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Many studies have reported that positively charged materials can be combined with negatively charged genes and nucleic acids through electrostatic adsorption to form drug-carrying nanocomplexes for the effective delivery of genes and nucleic acids [ 36 ]. Wang et al [ 37 ] prepared a multifunctional nanoparticle based on quantum dots (CDs) and modified β-cyclodextrin (β-CD) and arginine-glycine–aspartate (RGD) peptides. The nanocarrier can not only carry the small-molecule chemotherapeutic drug 5-fluorouracil (5-FU) through the hydrophobic cavity of β-CD, but also adsorb the electronegative siRNA (miR-10b inhibitor) through the positive electronegativity of the RGD peptide.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that positively charged materials can be combined with negatively charged genes and nucleic acids through electrostatic adsorption to form drug-carrying nanocomplexes for the effective delivery of genes and nucleic acids [ 36 ]. Wang et al [ 37 ] prepared a multifunctional nanoparticle based on quantum dots (CDs) and modified β-cyclodextrin (β-CD) and arginine-glycine–aspartate (RGD) peptides. The nanocarrier can not only carry the small-molecule chemotherapeutic drug 5-fluorouracil (5-FU) through the hydrophobic cavity of β-CD, but also adsorb the electronegative siRNA (miR-10b inhibitor) through the positive electronegativity of the RGD peptide.…”
Section: Introductionmentioning
confidence: 99%